Check-list of additional taxa to the supplement flora of Turkey IX - Ozhatay, Neriman; Kultur, Sukran; Gurdal, Bahar (Istanbul Univ, Fac Pharmacy, 2019)
The ninth of the check-list series entitled Check-list of additional taxa to the supplement flora of Turkey includes 159 taxa based on 120 papers published the period between January 2017 and December 2018. These taxa have not been recorded in none of the 11 volumes of the Flora of Turkey nor in the eight previously published supplementary check-lists. With this paper the following are added to the Turkish flora: 117 taxa new to science and 42 taxa new records.
Keywords: Additional taxa; Turkish flora; new species; new records